Viabilidade financeira da produção de milho por meio do manejo integrado de pragas na Chapada do Apodi, em Limoeiro do Norte-Ce - Peixoto, Maria Luíza Lima Ferreira (2015)
The culture of maize (Zea Mays), during its growth and development, is subjected to various management practices in order to avoid productivity losses attack of pests, diseases, and weed interference. Especially the production losses caused by the fall armyworm (Spodoptera frugiperda S.), his presence affect plant development and grain quality, being controlled through the application of agrochemicals such as insecticides. From the need to identify viable management alternatives to maize for the AG-1051 hybrid, not only for its environmental aspect, but the financial expectations, this paper makes a comparison of agronomic and financial characteristics of the viability of production maize with Integrated Pest Management (IPM), comparing it with the production of maize held conventionally, in the region of the Irrigated Perimeter Jaguaribe-Apodi in the town of Limoeiro do Norte. We conducted a field experiment to collect deployment cost data, cultivation, production, and sales price of the maize market, and productivity of both the production of the IPM as the conventional production. These data were for a horizon of analysis of ten (10) years. The financial analysis consisted in the construction of a cash flow for the situations with and without financing, two different scenarios and two different credit simulations, to produce one and two acres in both production systems. Based on the financial viability indicators (BCR, NPV and IRR), maize produced with the IPM performed better when compared with the conventional system. It held still a sensitivity analysis to measure the variation in revenues and costs, in order to better compare the two production systems. The analysis demonstrated that the IPM even having a lower productivity when explored in an area of two hectares of production for Scenarios I, got greater profitability and shorter capital recovery. Both systems did not show satisfactory results for Scenario II, which was considered the purchase of a fertilizer-sowing machine.